Solid‐based disperser liquid–liquid microextraction for the preconcentration of phthalate esters and di‐(2‐ethylhexyl) adipate followed by gas chromatography with flame ionization detection or mass spectrometry. Issue 9 (13th April 2014) - Farajzadeh, Mir Ali; Khorram, Parisa; Nabil, Ali Akbar Alizadeh
<x xml:space="preserve">Abstract</x> A new approach for the development of a dispersive liquid–liquid microextraction followed by GC with flame ionization detection was proposed for the determination of phthalate esters and di‐(2‐ethylhexyl) adipate in aqueous samples. In the proposed method, solid and liquid phases were used as the disperser and extractant, respectively, providing a simple and fast mode for the extraction of the analytes into a small volume of an organic solvent. In this method, microliter levels of an extraction solvent was added onto a sugar cube and it was transferred into the aqueous phase containing the analytes. By manual shaking, the sugar was dissolved and the extractant was released into the aqueous phase as very tiny droplets to provide a cloudy solution. Under optimized conditions, the proposed method showed good precision (RSD less than 5.2%), high enrichment factors (266–556), and low LODs (0.09–0.25 μg/L). The method was successfully applied for the determination of the target analytes in different samples, and good recoveries (71–103%) were achieved for the spiked samples. No need for a disperser solvent and higher enrichment factors compared with conventional dispersive liquid–liquid microextraction and low cost and short sample preparation time are other advantages of the method.